Examining the Constitutional Court’s Positive Legislature Decisions in Indonesia's Hierarchy of Legal Norms - Labib Muttaqin; Nunik Nurhayati; M. Junaidi; Rochman Hadi Mustofa; Amaylia Noor Alaysia (Jurnal Jurisprudence, 2024)
ABSTRACT Purpose of the study: The objective of this research is to investigate the positive legislature decision of the Constitutional Court, whose hierarchy is ambiguous in the order of Indonesian legal norms. Methodology: This study utilized a doctrinal legal research method with a legal realism approach. The data were sourced from primary, secondary, and tertiary legal materials. The authors employed the literature study as the method to collect data that were then qualitatively analysed. Results: The results of this study indicate that from a formal perspective, the positive legislature decision is a court verdict that falls under the jurisdiction of the judicial branch of power. However, from a material perspective, it encompasses elements such as regulations (regeling) that are genuinely located within the executive and legislative branches of power. Considering the presence of norms (regeling) in the Positive Legislature Decision, it is necessary to evaluate its position within the hierarchy of legal norms in Indonesia. Applications of this study: Constitutional judges can use this research as a reference in making positive legislative decisions. It can also be used as a reference in forming laws as a follow-up to the Constitutional Court's decision. Novelty/Originality of this study: This research revealed that the Constitutional Court's positive legislature decision includes elements of legal norms, also known as regeling, such as statutory regulations. Consequently, it is imperative to evaluate the position of courtly decisions within the hierarchical structure of legal norms in Indonesia. It is also crucial to find the legal reasoning for the Constitutional Court's positive legislature decision. Keywords: Constitutional Court Decisions, Positive Legislature, Legal Norms, Legal Hierarchy   ABSTRAK  Tujuan Penelitian: Penelitian ini bertujuan untuk mengkaji putusan perundang-undangan positif Mahkamah Konstitusi yang hierarkinya masih rancu dalam tatanan norma hukum Indonesia. Metodologi: Penelitian ini menggunakan metode penelitian hukum doktrinal dengan pendekatan realisme hukum. Data yang digunakan bersumber dari bahan hukum primer, sekunder, dan tersier. Metode pengumpulan data dilakukan dengan studi kepustakaan yang kemudian dianalisis secara kualitatif. Hasil Penelitian: Hasil penelitian ini menunjukkan bahwa dari segi formil, putusan perundang-undangan positif merupakan putusan pengadilan yang berada di bawah yurisdiksi cabang kekuasaan yudikatif. Namun, dari segi materiil, putusan perundang-undangan positif mengandung unsur-unsur seperti peraturan perundang-undangan (regeling) yang secara hakiki berada di bawah cabang kekuasaan eksekutif dan legislatif. Melihat keberadaan norma (regeling) dalam Putusan Perundang-Undangan Positif, maka perlu dikaji kedudukannya dalam hierarki norma hukum di Indonesia. Aplikasi Penelitian: Hasil penelitian ini dapat dijadikan acuan bagi hakim konstitusi dalam mengambil keputusan perundang-undangan positif. Dapat pula dijadikan sebagai acuan dalam pembentukan peraturan perundang-undangan sebagai tindak lanjut putusan Mahkamah Konstitusi. Kebaruan/Keaslian penelitian ini: Penelitian ini mengungkap bahwa putusan MK yang bersifat positif mengandung unsur norma hukum, yang juga dikenal dengan istilah regeling, seperti peraturan perundang-undangan. Oleh karena itu, penting untuk mengevaluasi kedudukan putusan pengadilan dalam struktur hierarki norma hukum di Indonesia. Penting pula untuk menemukan alasan hukum di balik putusan MK yang bersifat positif tersebut. Kata Kunci: Putusan MK, Legislatif Positif, Norma Hukum, Hirarki Hukum